OPTIMASI BIAYA OPERASIONAL PADA KRL COMMUTER LINE DENGAN PEMBERANGKATAN KERETA - Luciana, Shelen; Aman, Amril; Bakhtiar, Toni (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2020)
Optimal trainset dispatching can reduce passenger build-up and optimize operational costs. This research aimed to create a model of trainset dispatching for each time slot with minimum operational costs so that passenger demand can be met. The parameters in this research are the number of passengers getting-on and getting-off, the availability of each type of train series, train capacity, operational costs, and time limits for using the training series during operational hours. The model was formed into integer linear programming and resolved with Lingo 11.0 software. This model is applied in one direction from Bogor station to the Jakarta Kota commuter line. Trainset dispatching is done by selecting the 8 SF, 10 SF, and 12 SF trainset types with minimum operational costs at each time slot. The optimum results obtained during operational hours need to dispatch 56 trainset trips. Due to the limitations of the study the optimum operational cost of trainset dispatched is obtained 302C.